Design and Finite Element Model of a Microfluidic Platform with Removable Electrodes for Electrochemical Analysis. Issue 2 (1st February 2019) - Molina, Daniel E.; Medina, Adan Schafer; Beyenal, Haluk; Ivory, Cornelius F.
Abstract : A microfluidic platform for hydrodynamic electrochemical analysis was developed, consisting of a poly(methyl methacrylate) chip and three removable electrodes, each housed in 1/16" OD polyether ether ketone tube which can be removed independently for polishing or replacement. The working electrode was a 100-μm diameter Pt microdisk, located flush with the upper face of a 150 μm × 20 μm × 3 cm microchannel, smaller than previously reported for these types of removable electrodes. A commercial leak-less reference electrode was utilized, and a coiled platinum wire was the counter electrode. The platform was evaluated electrochemically by oxidizing a potassium ferrocyanide solution at the working electrode, and a typical limiting current behavior was observed after running linear sweep voltammetry and chronoamperometry, with flow rates 1−6 μL/min. While microdisk channel electrodes have been simulated before using a finite difference method in an ideal 3D geometry, here we predict the limiting current using finite elements in COMSOL Multiphysics 5.3a, which allowed us to easily explore variations in the microchannel geometry that have not previously been considered in the literature. Experimental and simulated currents showed the same trend but differed by 41% in simulations of the ideal geometry, which improved when channel and electrode imperfections were included.